TYPIFICATION OF TECTARIA PARADOXA (POLYPODIACEAE SUB-FAM. TECTARIOIDEAE) - Jaideep Mazumdar (Reinwardtia, 2017)
MAZUMDAR, J. 2017. Typification of Tectaria paradoxa (Polypodiaceae subfam. Tectarioideae). Reinwardtia 16(2): 93-95. — Aspidium paradoxum has not yet been lectotypified, because the original material is ambiguous. A specimen from the collections of A. Fée, the author of the species, was located in the herbarium of Montpellier (MPU), which is here designated as the lectotype for this species. It is now known as Tectaria paradoxa, a fern species widely distributed across tropical Asia.